2012
DOI: 10.1080/15427609.2012.680843
|View full text |Cite
|
Sign up to set email alerts
|

In-Law Relationships Before and After Marriage: Husbands, Wives, and Their Mothers-in-Law

Abstract: Relationships with in-laws play an important role in individuals’ lives, but we do not know how these ties are formed. We considered two pathways through which early relationships with mothers-in-laws may affect subsequent in-law relationship qualities: a) dimensions of the early relationship and, b) beliefs and expectations of the future relationship. Sixty men and women engaged to be married and their mothers (N = 240) completed interviews prior to, and 6 to 8 months following the wedding. Measures at Time 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
3
25
1
3
Order By: Relevance
“…In marriage we almost inevitably form social ties to nonblood family members whom we were less likely to form ties to in the absence of marriage. By being our loved one's direct family, in‐laws tend to become important to us and to the inner dynamics of marriage (Fingerman et al., ; Turner, Young, and Black, ; Willson, Shuey, and Elder, ). Paraphrasing insights reported in the family literature, in‐laws may provide a series of social support functions and one might feel both solidarity with and ambivalence about them because of the familial tie (Fingerman, Sechrist, and Birditt, ).…”
Section: Marriage In‐laws and Crimementioning
confidence: 99%
See 1 more Smart Citation
“…In marriage we almost inevitably form social ties to nonblood family members whom we were less likely to form ties to in the absence of marriage. By being our loved one's direct family, in‐laws tend to become important to us and to the inner dynamics of marriage (Fingerman et al., ; Turner, Young, and Black, ; Willson, Shuey, and Elder, ). Paraphrasing insights reported in the family literature, in‐laws may provide a series of social support functions and one might feel both solidarity with and ambivalence about them because of the familial tie (Fingerman, Sechrist, and Birditt, ).…”
Section: Marriage In‐laws and Crimementioning
confidence: 99%
“…The results of research have shown that the relationship to in‐laws is important for the marital ties between the spouses (Fingerman et al., ) because it is often characterized by ambivalence (Turner, Young, and Black, ; Willson, Shuey, and Elder, ). The married couples’ relationship success may depend on the relationship to the in‐laws (Bryant, Conger, and Meehan, ; Högnäs and Carlson, ).…”
mentioning
confidence: 99%
“…Although middle-aged wives tend to give more frequent emotional support to parents-in-law, research indicates that wives and husbands spend a similar amount of time giving practical assistance to parents-in-law at midlife (Chesley & Poppie, 2009). Husbands and wives have closer ties with their parents compared to their parents-in-law (Fingerman, Gilligan, VanderDrift, & Pitzer, 2012). Consequently, help given to parents-in-law may be more likely to be perceived as interference in the marriage.…”
Section: Future Directionsmentioning
confidence: 99%
“…Due to the increased life expectancy and longer shared lives of aging parents and adult offspring, most married adult children are likely to provide support for both their aging parents and their parents-in-law. Thus, providing informal support for a parent-in-law has become common among middle-aged adults [1, 2]. Recently, scholars have started to pay more attention to in-law relationships in an effort to explore the implications of intergenerational relationships for the marital relationships of adult children [3, 4].…”
Section: Introductionmentioning
confidence: 99%